TINJAUAN YURIDIS SOSIOLOGIS TERHADAP PENERAPAN FUNGSI ASESMEN DALAM PUTUSAN REHABILITASI PERKARA TINDAK PIDANA NARKOTIKA DI PENGADILAN NEGERI SUKOHARJO - FITRIASTUTI, EVI (Dinamika Hukum, 2016)
The purpose of this research is to know the application of assessment function in decision of rehabilitation of narcotic crime case in Sukoharjo District Court. In addition, it wants to know the obstacles that exist in the implementation of assessment function in the decision of rehabilitation of narcotic criminal case case in Sukoharjo District Court. The method of research includes the type of sociological juridical research, data collection techniques in the form of assessment of legal documents and interviews with inductive data analysis techniques that draw conclusions from problems that are concrete (special) to obtain a conception and norms of a general nature. The result of the research shows that the assessment function in the decision of rehabilitation of narcotic drug case in the Sukoharjo District Court has been applied in the trial process as one of judge's consideration in deciding the rehabilitation decision. However, its application is highly dependent on the presence or absence of an assessment request for the defendant in the case. A common obstacle in the practice of applying the assessment function is that there is no clear regulatory legislation on the assessment, which creates legal uncertainty resulting in disparities in the assessment as a basis for judges' consideration in imposing rehabilitation decisions. In addition there is no uniformity in terms of standardization of mechanisms and assessment results that are considered eligible as legal evidence according to the law. Keywords : The application of assessment function in decision of rehabilitation crime case in Sukoharjo District